2011
DOI: 10.1086/660775
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Liquid Housing Wealth on College Enrollment

Abstract: This article uses short-run housing wealth changes to identify the effect of housing wealth on college attendance. I find that households used their housing wealth to finance postsecondary enrollment in the 2000s when housing wealth was most liquid; each $10,000 in home equity raises college enrollment by 0.7 of a percentage point on average. The effect is localized to lower-resource families, for whom a $10,000 increase in housing wealth increases enrollment by 5.7 percentage points. These estimates imply tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
165
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(182 citation statements)
references
References 17 publications
6
165
0
3
Order By: Relevance
“…6 Lovenheim (2011) shows that, particularly for relatively low-income families, changes in housing wealth have a substantial effect on enrollment. In contrast, Hilger (2012) demonstrates that parental income has a relatively small negative effect on enrollment using the timing of layoffs.…”
Section: Postsecondary and Labor Market Policies Affecting Enrollmentmentioning
confidence: 99%
“…6 Lovenheim (2011) shows that, particularly for relatively low-income families, changes in housing wealth have a substantial effect on enrollment. In contrast, Hilger (2012) demonstrates that parental income has a relatively small negative effect on enrollment using the timing of layoffs.…”
Section: Postsecondary and Labor Market Policies Affecting Enrollmentmentioning
confidence: 99%
“…Early studies tended to find that credit constraints were not prevalent (Cameron and Heckman, 1998;Cameron and Taber, 2004;Carneiro and Heckman, 2002;Keane and Wolpin, 2001). However, recent studies have shown borrowing constraints matter for educational investment (Belley and Lochner, 2007;Brown et al, 2012;Cowan, 2016;Lovenheim, 2011;Stinebrickner and Stinebrickner, 2008) .…”
Section: Credit Constraintsmentioning
confidence: 99%
“…Lovenheim (2011) …nds that households used their housing wealth to …nance postsecondary enrollment in the 2000s when housing wealth was most liquid. This …nding implies that the recent housing bust could signi…cantly a¤ect college enrollment through the reduction in housing wealth of families with college-age children.…”
Section: Introductionmentioning
confidence: 99%